Kekerasan Terhadap Perempuan dan Nilai Pendidikan Karakter Dalam Novel Bak Rambut Dibelah Tujuh Karya Muh. Makhdlori Serta Relevansinya Dengan Pembelajaran Bahasa Indonesia - Ismanto Ismanto; Aditya Budi Purnomo (Universitas Palan, 2024)
This research aims to describe forms of violence against women in novels, the value of character education in novels, and its relevance to Indonesian language learning in high school. This research uses a qualitative descriptive method with a feminist approach through Mansoer Fakih's feminist theory. The source of research data is the novel Bak Rambut Dibelah Tujuh by Muhammad Makhdlori and informants. Data collection techniques using document analysis and informant interviews. Data validity techniques with data using data triangulation. Data analysis techniques using interactive analysis models. Based on the results of the analysis, it is known that violence against women is dominated by emotional violence. Found the value of character education in the novel. Religious character values and social care are the dominant values that appear in the novel.